Use of qualitative control and discriminatory function in applied studies - Marwan Dabdoub; Omer Al-Rawi (College of Education for Pure Sciences, 2007)
ABSETRACT Shewhart control chart is used to control the quality of a process of a variable in a specific stage, if the chart is frequently constructed under different stages, we suggested to construct a pooled control charts, the aim of the pooling is to compare the path of the observations in the different stages. Whenever more than one variable affect the studied phenomena, we suggested to construct the quality control chart by using the discriminant function. The characters of the suggested methods were mentioned and applied study was discussed.